1991
DOI: 10.1007/bf01923334
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors in neurotoxicology and neuropharmacology: A critical evaluation of the use of genetics as a research tool

Abstract: Animals have evolved a detoxication system to enable them to survive in a hostile chemical environment in which foods contain many non-nutrient chemicals. Detoxication depends on enzymes which are often genetically polymorphic. As a result, inter-individual variation is common, and in humans several Mendelian loci have been identified. However, most variation in response is probably due to the action of several genes. Genetic variation in response to the neurotoxin MPTP and to chemically and physically-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Although albinism is the result of a lack of melanin pigments, the absence of melanin in mice produced by a point mutation in the gene for tyrosinase, the enzyme that catalyzes the first two steps of melanin synthesis, located on chromosome 7, did not protect the mice from MPTP-induced behavioral deficits, DA depletion in the striatum, and neuron loss in the SNpc [107]. The possibility that the higher sensitivity to MPTP observed in pigmented mice [105, 108] is caused by a susceptibility gene located in the same chromosomal region warrants further investigation.…”
Section: Not All Mouse Strains Are Vulnerable To the Toxic Effects Ofmentioning
confidence: 99%
“…Although albinism is the result of a lack of melanin pigments, the absence of melanin in mice produced by a point mutation in the gene for tyrosinase, the enzyme that catalyzes the first two steps of melanin synthesis, located on chromosome 7, did not protect the mice from MPTP-induced behavioral deficits, DA depletion in the striatum, and neuron loss in the SNpc [107]. The possibility that the higher sensitivity to MPTP observed in pigmented mice [105, 108] is caused by a susceptibility gene located in the same chromosomal region warrants further investigation.…”
Section: Not All Mouse Strains Are Vulnerable To the Toxic Effects Ofmentioning
confidence: 99%
“…Programs of selective breeding have produced a strain or stock that has unique qualities such as sensitivity to certain drugs, pathological susceptibility, and other sequelae (Festing, 1993). To this end, Festing (1991) suggested that inbred strains are genetically more uniform and should exhibit a less varied response to neurotoxic agents. Isogenic inbred strains would be more amenable to toxicological screening because the genetic variation of outbred strains obscures the true treatment effects (Festing, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Most animal studies use only a single strain of mice or rats so that genetic variations in response are not noted; however, several studies have shown strain differences among laboratory animals in response to a wide range of xenobiotics including neurotoxic agents. For example, strain differences in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) neurotoxicity in mice have been reported and have been associated with differences in melanin binding or monoamine oxidase activity (40,41). Genetic influences in the developmental neurotoxicity of alcohol are also apparent (42 (51).…”
Section: Biomarers Ofsusceptibilitymentioning
confidence: 99%